Analisis Perbedaan Implementasi Kebijakan Tunjangan Kinerja dengan Kebijakan Remunerasi (Studi Kasus di Politeknik Negeri) - Wijarti, Kusindianing; Sawitri, Dyah; Joesoef, Jose Rizal (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2026)
Since 2012, Malang State Polytechnic has become one of the Government Universities (PTP) that has implemented Public Service Agency Financial Management (PK-BLU). The PK-BLU pattern provides flexibility in the use of PNBP funds. One of the policies implemented as a consequence of Malang State Polytechnic (POLINEMA) becoming a PTN BLU is to implement a remuneration policy. This policy has been implemented since 2016, whereas previously as a government agency, POLINEMA implemented a performance allowance policy. Based on empirical facts that are also supported by existing theories, the purpose of the study is to analyze the differences in the implementation of performance allowance policies with remuneration policies and their relationship to the performance of Civil Servants (PNS) at the State Polytechnic of Malang. This study uses a qualitative approach. using a case study research type and the data analysis used is the Miles and Huberman mode data analysis method. According to the Regulation of the Minister of Administrative and Bureaucratic Reform Number 15 of 2008 concerning General Guidelines for Bureaucratic Reform, the implementation of remuneration has three targets, namely: changes in mindset, work culture, and work behavior. However, the results in its implementation are still far from expectations. This is shown from the recapitulation of performance assessment data for education personnel in 2016, the data shows that there has been no significant change related to employee performance with the implementation of remuneration at the State Polytechnic of Malang.